How have employment transitions for older workers in Germany and the UK changed? - David Wright (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Extending working life is an objective for many nations. However, the UK government has recently reported only modest improvement "compared to many nations". A comparison of European, Labour Force Surveys show that Germany has reversed early retirement much faster than the UK since 2003. This was not forecast by previous researchers. In particular, Ebbinghaus' influential cross-national analysis of early retirement, published in 2006, had predicted that liberal welfare states regimes like the UK would react faster than conservative ones like Germany. A review of changes to pensions and employment policies suggests the UK puts more emphasis on recruitment of older workers, flexible working and gradual retirement while Germany puts more emphasis on retention of older workers through age-management and employment protection. The paper compares the employment transitions of older workers using data covering 1993 to 2013 from the longitudinal surveys British Household Panel Survey, Understanding Society and the German Socio-Economic Panel. It finds little evidence for the recruitment of older workers or gradual retirement in either the UK or Germany and concludes it was the greater employment protection for older workers in Germany that enabled the employment rate for older workers to increase even during the recent recession.
Keywords: J21; 330; Older workers; United Kingdom; Germany